Гость :

ПОМОГИТЕЕЕ

1. (tg a + ctg a) * sin a * cos a
2. sin^2 a * cos^2 a (tg^2 a + ctg^2 a + 2)

11 дней назад

Лучший ответ:


Loading...

(tg  /alpha +ctg /alpha )/cdot /sin /alpha /cos /alpha =tg /alpha /sin /alpha /cos /alpha +ctg /alpha /sin /alpha /cos /alpha =// // =/sin^2 /alpha +/cos^2 /alpha =1


/sin^2 /alpha /cos^2 /alpha (tg^2 /alpha +ctg^2 /alpha +2)=/sin^2 /alpha /cos^2 /alpha (tg /alpha +ctg /alpha )^2=// // =(tg /alpha /sin /alpha /cos /alpha +ctg /alpha /sin /alpha /cos /alpha )^2=(/sin^2 /alpha +/cos^2 /alpha )^2=1^2=1

11 дней назад


 
 

Другие вопросы:


Гость :
11 дней назад
resp. 9.571 ms | lastmod 2020-03-26 08:26:48